2011
DOI: 10.1007/s10531-011-0090-4
|View full text |Cite|
|
Sign up to set email alerts
|

Protective management of trees against debarking by deer negatively impacts bryophyte diversity

Abstract: When wildlife populations become too large, they impact other flora and fauna within the ecosystems that they inhabit. For example, the recent rise in population numbers of sika deer in Japan has led to the stripping of bark from tree overstories in forested areas.This has led to protective management actions, such as wrapping the trunks of trees in wire mesh. The present study investigates the impact of this management action on epiphytic diversity at Mt. Ohdaigahara, which is one of the hotspots for bryophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…1 and Table 1, respectively. These plots were identical to those used in previous studies (Oishi 2011(Oishi , 2012(Oishi , 2013(Oishi , 2014; however, the names of plots were changed from those used in previous reports to adjust to the context of the present study. …”
Section: Plot Locationsmentioning
confidence: 98%
See 1 more Smart Citation
“…1 and Table 1, respectively. These plots were identical to those used in previous studies (Oishi 2011(Oishi , 2012(Oishi , 2013(Oishi , 2014; however, the names of plots were changed from those used in previous reports to adjust to the context of the present study. …”
Section: Plot Locationsmentioning
confidence: 98%
“…These practices include control of the deer population via culling, erection of deer-proof fences, and wrapping trees with wire mesh to protect against bark stripping (MOE 2009). Notably, among these practices, Oishi (2011) revealed that wrapping trees with wire mesh can cause metal pollution, which in turn leads to a decrease in the diversity of epiphytic bryophytes. In subsequent reports, Oishi (2012) suggested that, compared with the 1980s, the species richness of epiphytic bryophytes was declining on Mt.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 9 plots (each 20 × 20 m in size) were selected ( Fig. 1 A-I; Table 2) to examine the influence of wire mesh protection on epiphytic bryophyte diversity The names of plots were changed from those used in previous reports (Oishi, 2011) to adjust to the context of the present study. Plots A-D were identical to those mentioned in section 2.4.…”
Section: Site Selectionmentioning
confidence: 99%
“…Table 3. Generalized liner models showing the association of species richness and bryophyte cover with environmental variables (Oishi, 2011). The significance level of the coefficients and adjusted R 2 values are shown.…”
Section: Analysis Of Zinc Concentrationmentioning
confidence: 99%
See 1 more Smart Citation